Influence of Emoji Use in Online Media Communication (Whatsapp) on User Reactions and Responses - Sayyid Musafa Alwan; Suci Zuriati; Norma Amaliyah; Putri Maharani; Jahirun Manik; Fazri Fadhilah Tambunan (Yayasan Al'Adzkiya Rantauprapat, 2024)
The purpose of this study is to determine the impact of emoji use in online communication, specifically through the WhatsApp platform, on users' reactions and responses. As the use of digital communication becomes more widespread, emoji are becoming an important element in text conversations, helping to convey emotions and intentions that are not always obvious through text alone. This study uses a quantitative survey method to collect data from WhatsApp users about their perceptions and experiences when using emoji. The study shows that the use of emoji has a significant impact on the interpretation of messages, improving the clarity of communication and strengthening social relationships between users. In addition, emoji were shown to reduce misunderstandings and speed up responses in conversations. These findings suggest that emoji can serve as an effective communication tool to improve the quality of digital interactions. This study provides important insights for instant messaging app developers and digital communication researchers, and paves the way for further research into the role of emoji in different online communication contexts.